Novel IEEE802.15.4 protocol for modern SCADA communication systems - Shabani, Hikma; Ahmed, Musse Mohamud; Khan, Sheroz; Hameed, Shihab A.; Habaebi, Mohamed Hadi; Zyoud, Alhareth (IEEE Computer Society, 2014)
Supervisory Control and Data Acquisition (SCADA) system is a computer system for collecting and analysing data in almost real-time fashion for monitoring and control of electric powersystem applications.Thus, communication channels play a core role in SCADA systems implementation. The use of wireless sensor network (WSN) communication can, however, lead to a more flexible and powerful electric power systemprotection scenarios than the current used wired sensor.Hence, in order to provide a real-time data exchange in Low Voltage Smart Grid Distribution Systems and thus, predict a Real-time electric power system control, a Novel IEEE802.15.4 Protocol aimed atWSN for Modern SCADA Communication System is modeled in this paper. The protocol performance is evaluated using NS-2 Simulation and the preliminary results are encouraging.